Experimental investigation on the response and residual compressive property of honeycomb sandwich structures under single and repeated low velocity impacts. (December 2020) - Dai, Xiangjun; Yuan, Tianyu; Zu, Zheng; Ye, Hangyu; Cheng, Xiangmeng; Yang, Fujun
Abstract: Single and repeated impact tests were carried out on honeycomb sandwich structures. The effect of varying impact energy levels and numbers on impact response, damage parameters, and energy absorption was studied. During these tests, the time histories of contact forces, deflections, and impact energies were recorded in real time. Three-dimensional digital image correlation (3D-DIC) was applied to obtain the dent depths, damage areas, and damage volumes of front and rear surfaces. The residual compressive properties of the above-mentioned structures were determined using compression after impact tests and 3D-DIC. Further, the onset of damage procession and failure modes were analyzed. A finite element model was performed to characterize the impact response of honeycomb sandwich structures. The simulation results was in good agreement with experimental data, which indicated the model could be used for the simulation on aluminum honeycomb sandwich panels subjected to single and repeated low-velocity impacts.